Application of Malmquist indices in valuation process of adult day surgery system in Slovakia - Beata Gavurova; Samuel Korony (European Financial and Accounting Journal, 2016)
In developed countries, day surgery has been used as a significant tool of efficiency increase in the health care system over the last few decades. However, its development is not sufficient in the Slovak conditions in spite of the support of the Ministry of Health of the Slovak Republic. Its use in the unstable conditions of the Slovak health system represents the main reason. The paper presents a partial output of the research that focuses on day surgery development in order to increase an efficiency of the health system in Slovakia. Its primary aim is to highlight a significance of Malmquist indices' application in evaluation of day surgery processes of adult patients. The outputs represent a valuable platform for health and social policies' creators.
Keywords: C61; H51; 650; Day Surgery; Day Surgery Efficiency; Health System Efficiency; Malmquist Indices